2020
DOI: 10.1108/jima-12-2019-0255
|View full text |Cite
|
Sign up to set email alerts
|

Resource-capability of halal logistics services, its extent and impact on performance

Abstract: Purpose The purpose of this paper is to examine the extent of emergent resource-capability, its configurations and its impacts on customer service innovation and cost advantages in the context of the halal dynamic environment. Design/methodology/approach The study performed a cluster analysis on a sample of 123 Malaysian halal-based third-party logistics (3PL) providers. Findings The findings reveal that the emergent resource-capability comprising physical, technology, knowledge, relational and organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
(106 reference statements)
1
13
0
Order By: Relevance
“…Besides, Salindal (2019) also adds that halal certification and innovation include important components such as quality and security of halal food which in turn can influence the company image and reputation. This is in agreement with the study of Noorliza (2021) stating that the resources arising from halal logistic products in halal industrial era will move fast and be able to lever the company competitiveness. Therefore, halal product providers can develop their resources in the forms of physical, technology, knowledge, relations, and organization to boost the success of their halal products which should be further innovated in the dynamic halal environment.…”
Section: Influence Of Halal Certification On Innovationsupporting
confidence: 91%
“…Besides, Salindal (2019) also adds that halal certification and innovation include important components such as quality and security of halal food which in turn can influence the company image and reputation. This is in agreement with the study of Noorliza (2021) stating that the resources arising from halal logistic products in halal industrial era will move fast and be able to lever the company competitiveness. Therefore, halal product providers can develop their resources in the forms of physical, technology, knowledge, relations, and organization to boost the success of their halal products which should be further innovated in the dynamic halal environment.…”
Section: Influence Of Halal Certification On Innovationsupporting
confidence: 91%
“…Karia [27], using quantitative techniques, established that HL integration positively affects Halal logistics performance. Noorliza [28], with empirical evidence, suggested that the resource-capability of HL services can make Halal LSPs more competitive.…”
Section: Research Methods and Background Modelmentioning
confidence: 99%
“…Moreover, published halal logistics literature has examined various logistical activities such as in packaging (Talib and Johan, 2012), transportation (Ngah et al, 2019), warehousing (Ngah et al, 2015) and purchasing . More recently, scholars study halal logistics in newer contexts such as service innovation (Noorliza, 2020), logistics integration (Karia, 2019) and blockchain technology (Tieman et al, 2019).…”
Section: Halal Logisticsmentioning
confidence: 99%